2018
DOI: 10.3906/sag-1704-92
|View full text |Cite
|
Sign up to set email alerts
|

e impact of visit-to-visit systolic blood pressure variability on residual renal function and le ventricular hypertrophy in peritoneal dialysis patients

Abstract: Background/aim: Blood pressure (BP) variability is more closely associated with adverse outcomes than 'usual' BP in the general population. Residual renal function (RRF) and left ventricular hypertrophy (LVH) are thought to be predictors of poor outcome in dialysis patients. However, only a few studies have focused on BP variation and its link to RRF, LVH, and outcome in peritoneal dialysis (PD) patients. Therefore, we aimed to explore the effect of visit-to-visit BP variability on RRF and LVH in continuous am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Studies have shown that echocardiography can evaluate the characteristics of left ventricular thickness, left ventricular volume, and wall motion, and it is a widely used auxiliary examination method for judging left ventricular diastolic function in the clinic [ 9 ]. The heart rate of mice is generally between 300-500 BPM, and the ventricular cavity is small, so ordinary echocardiography cannot obtain a clear image [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that echocardiography can evaluate the characteristics of left ventricular thickness, left ventricular volume, and wall motion, and it is a widely used auxiliary examination method for judging left ventricular diastolic function in the clinic [ 9 ]. The heart rate of mice is generally between 300-500 BPM, and the ventricular cavity is small, so ordinary echocardiography cannot obtain a clear image [ 10 ].…”
Section: Introductionmentioning
confidence: 99%